PERANCANGAN SISTEM KEANGGOTAAN GYM GLADIATOR BERBASIS WEB: MENINGKATKAN PENGALAMAN PELANGGAN DAN EFISIENSI MANAJEMEN KEANGGOTAAN - Muhammad Rifqi Juniawan; Suhanda Saputra (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Gladiator Gym is a fitness center located at Ruko Dasana Xentre Block BD No. 20-22, Bojong Nangka, Kelapa Dua, Tangerang, Banten. Currently, Gladiator Gym has a large number of members. However, the data storage system for its members still relies on paper, making it inefficient and prone to damage or loss. Recognizing the weaknesses in the current membership data management system, this research aims to design a web-based membership system using MySQL as the database and PHP as the programming language. The purpose of this study is to assist in member record-keeping, computerize payment recording systems, and manage program packages. In developing this web-based information system, the author employs the System Development Life Cycle (SDLC) method, utilizing the Waterfall model. The result of this research is a web-based membership application. The system design is expected to provide a better experience for customers while accelerating and optimizing membership management operations at Gladiator Gym.